(untitled) (Edad Media. Revista de Historia, 2020)
The present work aims to study the use of spies and watchmen by the city of Valencia in the War of the Two Peters (1356-1366). To do this, after short terminological explanation, we have proceeded to explain the establishment of the surveillance systems of the territory and, mainly, the networks of spies woven in Castilian territory. The underlying issue is whether the city of Valencia made an intelligence system during the conflict with Castilla, an issue that has received a negative response after our analysis, which, however, reveals that initiatives were taken in that direction. The primary sources used for this work have come from the funds of the Arxiu Municipal de Valencia (AMV).